High Discounts and High Unemployment - Hall, Robert E. (American Economic Review, 2017)
Unemployment is high when financial discounts are high. In recessions, the stock market falls and all types of investment fall, including employers' investment in job creation. The discount rate implicit in the stock market rises, and discounts for other claims on business income also rise. A higher discount implies a lower present value of the benefit of a new hire to an employer. According to the leading view of unemployment—the Diamond-Mortensen-Pissarides model—when the incentive for job creation falls, the labor market slackens and unemployment rises. Thus high discount rates imply high unemployment. (JEL E24, E32, E44, J23, J31, J63)